STRATEGI GURU DALAM MENUMBUHKAN KREATIVITAS SISWA KELAS IV PADA MATA PELAJARAN SENI RUPA MATERI KOLASE - Sulistiana, Lisna; Abdurahman, Ayi (STKIP Subang, 2026)
This study aims to determine the strategies used by teachers to foster creativity in fourth-grade students in art classes through collage materials at SDN Pasirjati Elementary School and to identify the factors that support and hinder creativity. This study uses a qualitative approach with a descriptive method to gain an in-depth understanding of the learning process. The subjects of this study consist of fourth-grade teachers and fourth-grade students selected through purposive sampling. Data collection techniques included observation, interviews, literature study, and documentation, while data analysis used the Miles and Huberman model, which included the stages of data collection, data reduction, data presentation, and conclusion drawing and verification. The results showed that each teacher systematically planned teaching modules, used visual media, and applied a learning-by-doing model that emphasized hands-on practice. Collage learning using inorganic plastic waste had a positive impact on the development of students' creativity in both cognitive and non-cognitive aspects. Supporting factors included student interest and active participation, a conducive classroom atmosphere, and the availability of easily found materials, while inhibiting factors were related to differences in student characteristics and interests.